Universal Rapid Human Immunodeficiency Virus Screening at Delivery: A Cost-Effectiveness Analysis - Rachel K. Scott; Stacia Crochet; Chun-Chih Huang (Hindawi Limited, 2018)
Objective. To determine the cost-effectiveness of universal maternal HIV screening at time of delivery to decrease mother-to-child transmission (MTCT), by comparing the cost and quality-adjusted life years (QALYs) of universal rapid HIV screening at time of delivery to two current standards of care for prenatal HIV screening in the United States. Study Design. We conducted a cost-effectiveness analysis to compare the cost and QALY of universal intrapartum rapid HIV screening with two current standards of care: (I) opt-out rapid HIV testing limited to patients without previous third-trimester screening and (II) opt-out rapid HIV testing limited to patients without any prenatal screening. We developed a decision-tree model and performed sensitivity analyses to estimate the impact of variances in QALY, estimated lifetime medical costs, HIV prevalence, and cumulative incidence. Results. The incremental cost-effectiveness ratio for universal screening was $7,973.45/QALY. The results remained robust to sensitivity analysis, except for annual cumulative incidence. In areas with an annual cumulative incidence rate of <0.02% for reproductive-age women, the incremental cost-effectiveness ratio for the expanded program would exceed $89,926.94/QALY, approaching the commonly applied cost-effectiveness thresholds ($100,000/QALY). Conclusions. Intrapartum universal rapid HIV screening to decrease MTCT appears cost-effective in populations with high HIV incidence in the United States.